WACANA KEKERASAN DAN RESISTENSI PEREMPUAN DALAM FILM KARYA SUTRADARA PEREMPUAN - Dayanti, Liestianingsih Dwi (Jurnal Kawistara, 2011)
Mereka Bilang Saya Monyet, a movie by woman director Djenar Maesa Ayu, was a film about women with a different perspective. This movie reveals a discourse on both violence and womenâs resistance against it. The dimensions shown included psychological, physical, and sexual violence between parents and their child, an adult men with his daughter, and adult men with adult women. Violence appears because of the unbalanced relationship between subject and object. The effects of this violence can take the form of fear, anger, or a feeling of inferiority and unworthiness, and the victim feels encouraged to act on it. Discourse related to gender-based violence is a result of a patriarchal cultural construction. In the film, resistance was portrayed through the victimâs suffering, anger, and physical resistance. Women directors perceived these issues from a different perspective. It is not enough to understand violence against women only from the normative perspective of law and social obligation. This issue must be understood by positioning women as the subject (survivor) and recognizing that violence against women is a crime against humanity.